The Apaf-1 apoptosome induces formation of caspase-9 homo- and heterodimers with distinct activities - Chu-Chiao Wu (Nature Portfolio, 2016)
Apoptotic initiator caspases are thought to be activated through homodimerization but this remains controversial. Here the authors demonstrate that caspase-9 can adopt two distinct conformations within the Apaf-1 apoptosome, each with distinct properties that contribute to the overall function of the complex.